2023
DOI: 10.3390/biomedicines11030668
|View full text |Cite
|
Sign up to set email alerts
|

The Antibacterial Effect of Cannabigerol toward Streptococcus mutans Is Influenced by the Autoinducers 21-CSP and AI-2

Abstract: Bacteria can communicate through an intercellular signaling system referred to as quorum sensing (QS). The QS system involves the production of autoinducers that interact with their respective receptors, leading to the induction of specific signal transduction pathways. The QS systems of the oral cariogenic Streptococcus mutans regulate the maturation of biofilms and affect its virulent properties. We have previously shown that the non-psychoactive compound cannabigerol (CBG) of the Cannabis sativa L. plant ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…Novel non-euphoric cannabinoids, like cannabigerol (CBG), are concurrently gaining traction due to improved synthesis methods and changing public perception [6]. In fact, many recent studies of CBG in rodent models as well as human survey data suggest an increasing interest in using the compound to address human disease [7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Novel non-euphoric cannabinoids, like cannabigerol (CBG), are concurrently gaining traction due to improved synthesis methods and changing public perception [6]. In fact, many recent studies of CBG in rodent models as well as human survey data suggest an increasing interest in using the compound to address human disease [7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…The release of CBG from the coated meshes was efficient over a long period of time, and hence, the SRV-CBG is expected to provide prolonged protection. The reason why we chose CBG as the active compound in our study is that CBG has been shown to have both antibacterial and anti-inflammatory properties [ 29 , 37 , 40 , 41 , 59 , 60 ]. It is important to note that any mesh type can be used for our technology, but we focused here on VICRYL ® (polyglactin 910) mesh as a model because it is feasible, cost-effective, and clinically used in contaminated situations.…”
Section: Discussionmentioning
confidence: 99%
“…As far as its medical use is concerned, CBG has been proposed in therapies of prostate cancer (De Petrocellis et al, 2013) and glioblastoma (Lah et al, 2021), neuroprotection (García et al, 2018;Gugliandolo et al, 2018), antidiabetic action (Anokwuru et al, 2022), and in dermatology (Calapai et al, 2022). Furthermore, the antimicrobial activity of CBG has been suggested as beneficial in cases of topical skin disinfection due to the fact that it does not disturb the natural skin microbiota (Aqawi et al, 2023;Luz-Veiga et al, 2023).…”
Section: Discussionmentioning
confidence: 99%